Glass filler, its manufacturing method, and resin composition containing glass filler

A glass composition with optimized SiO2, B2O3, Al2O3, and RO contents addresses the challenge of low dielectric constant and mass production, improving resin composition properties in electronic devices.

JP7618550B2Active Publication Date: 2025-01-21NIPPON SHEET GLASS CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021526951
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-06-21
Filing Date
2020-06-19
Publication Date
2025-01-21
Estimated Expiration
2040-06-19

AI Technical Summary

Technical Problem

Existing glass fillers used in resin compositions for electronic devices have not adequately addressed the need for a low dielectric constant and suitable characteristic temperatures for mass production, making it difficult to meet the demands of smaller and more functional electronic devices.

Method used

A glass composition with specific ranges of SiO2, B2O3, Al2O3, and RO contents, along with optional oxides, is formulated to achieve a low dielectric constant and suitable viscosity for mass production, with dielectric constants of 4.4 or less and characteristic temperatures below 1700°C.

Benefits of technology

The glass filler improves resin composition properties by maintaining a low dielectric constant, enhancing strength, heat resistance, and dimensional stability while reducing linear thermal expansion and anisotropy, facilitating mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007618550000007
    Figure 0007618550000007
  • Figure 0007618550000008
    Figure 0007618550000008
  • Figure 0007618550000009
    Figure 0007618550000009
Patent Text Reader

Abstract

The present disclosure provides a novel glass filler which has low permittivity and is suitable for mass production. A glass filler provided herein includes a glass composition which contains, by wt%, for example, 40≤SiO2≤60, 25≤B2O3≤45, 0<Al2O3≤18, 0<R2O≤5, 0≤RO≤12, and in which at least one among i) SiO2+B2O3≥80, SiO2+B2O3+Al2O3≤99.9, and ii) SiO2+B2O3≥78, SiO2+B2O3+Al2O3≤99.9, 0<RO<10 is satisfied. Another glass filler provided herein includes a glass composition that contains SiO2, B2O3, Al2O3, and R2O, which respectively have the same contents as above, and 3<RO<8, and in which SiO2+B2O3≥75 and SiO2+B2O3+Al2O3<97 are satisfied. However, R2O equals Li2O+Na2O+K2O, and RO equals MgO+CaO+SrO.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a glass filler. The present invention also relates to a method for producing the glass filler and a resin composition containing the glass filler. [Background technology]

[0002] Resin compositions are widely used as electrical insulating materials and mechanical components in various electronic components. Examples of electrical insulating materials include connector housings used in SMT (surface mount technology), FPC (flexible printed circuits), board-to-board connections, CPU (central processing unit) sockets, memory cards, card edges, optical connectors, etc.; liquid crystal display (LCD) backlights; coils, flats, transformers, reactance bobbins used in magnetic heads, etc.; relay cases, relay base switches, reflow DIP switches, tactile switches, etc.; switches, sensor cases, capacitor casings, volume casings, trimmer casings, etc.; mechanical components include lens holders and pickup bases for optical pickups, insulators and terminals for micromotors, and laser printer drums. Resin compositions are also used as films, such as base films for FPCs and copper-clad laminates. One type of printed circuit board used in electronic components also includes substrates made of resin compositions. Printed wiring boards, before electronic components are mounted, also include substrates made of resin compositions. Hereinafter, in this specification, both printed circuit boards and printed wiring boards will be referred to as "printed boards."

[0003] The resin composition contains a thermoplastic resin and an inorganic filler, and may further contain a curing agent, a modifier, etc. as necessary. A glass filler may be used as the inorganic filler. A typical glass filler is glass flake. In recent years, in order to meet the demand for miniaturization of electronic devices and the demand for thinner devices for the purpose of higher functionality, resin compositions are required to have a low dielectric constant, and accordingly, the constituent materials thereof are also required to have a low dielectric constant.

[0004] Printed circuit boards may further contain glass fibers. These glass fibers are also required to have a low dielectric constant. Patent Documents 1 to 5 disclose glass fibers made from glass compositions with low dielectric constants. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 62-226839 [Patent Document 2] Special Publication No. 2010-508226 [Patent Document 3] Japanese Patent Application Laid-Open No. 2009-286686 [Patent Document 4] International Publication No. 2017 / 187471 [Patent Document 5] International Publication No. 2018 / 216637 Summary of the Invention [Problem to be solved by the invention]

[0006] However, research into lowering the dielectric constant of glass fillers has not progressed sufficiently. The glass composition for constituting the glass filler is required to have a characteristic temperature suitable for mass production as well as a low dielectric constant. The characteristic temperature of the glass composition important for mass production of glass fillers is the temperature T3, i.e., the temperature at which the viscosity is 10 3The temperature at which the dielectric constant reaches 1000 dPas is one example. The temperatures T2, T2.5, and even the devitrification temperature TL are also indicators for determining whether a glass composition is suitable for mass production of glass fillers. However, it is not easy to adjust the characteristic temperature of a glass composition with a low dielectric constant.

[0007] In view of the above, an object of the present invention is to provide a glass filler containing a novel glass composition that has a low dielectric constant and is suitable for mass production. [Means for solving the problem]

[0008] The present invention provides Expressed in weight percent, 40≦SiO2≦60 25≦B2O3≦45 5≦Al2O3≦15 0 <R2O≦5 0 <RO<15 Including, SiO2+B2O3≧80, and / or SiO2+B2O3≧78 and 0 <RO<10 The present invention provides a glass filler containing a glass composition in which the following holds true: In this specification, R2O is at least one oxide selected from Li2O, Na2O, and K2O, and RO is at least one oxide selected from MgO, CaO, and SrO.

[0009] From another aspect, the present invention provides Expressed in weight percent, 40≦SiO2≦60 25≦B2O3≦45 0 <Al2O3≦18 0 <R2O≦5 0≦RO≦12 Including, i) SiO2 + B2O3 ≥ 80, and SiO2 + B2O3 + Al2O3 ≤ 99.9, and ii) SiO2 + B2O3 ≥ 78, SiO2 + B2O3 + Al2O3 ≤ 99.9, and 0 <RO<10 The present invention provides a glass filler containing a glass composition, wherein at least one of the above conditions is satisfied.

[0010] From another aspect, the present invention provides Expressed in weight percent, 40≦SiO2≦60 25≦B2O3≦45 0 <Al2O3≦18 0 <R2O≦5 3 <RO<8 Including, SiO2+B2O3≧75, and SiO2+B2O3+Al2O3<97 The present invention provides a glass filler containing a glass composition in which the following holds true:

[0011] From another aspect, the present invention provides When expressed in weight percent, SiO2 + B2O3 ≥ 77 is satisfied, The dielectric constant at a frequency of 1 GHz is 4.4 or less, viscosity 10 2 The temperature T2 at which dPas is reached is 1700°C or less. The present invention provides a glass filler comprising a glass composition comprising:

[0012] From another aspect, the present invention provides The present invention provides a resin composition comprising the glass filler of the present invention and a thermoplastic resin.

[0013] From another aspect, the present invention provides The present invention provides a method for producing a glass filler, the method comprising the steps of melting the glass composition described above and forming the molten glass composition into a glass filler. The method for producing a glass filler may comprise the steps of melting glass raw materials prepared to obtain the glass composition described above that constitutes the glass filler, and forming the molten glass raw materials into the glass filler. [Effects of the Invention]

[0014] According to the present invention, it is possible to provide a glass filler containing a glass composition having a low dielectric constant and a characteristic temperature suitable for mass production. The glass filler according to the present invention is suitable for improving various properties of a resin composition by blending the glass filler while maintaining a low dielectric constant of the resin composition. The improvements include, for example, improved strength, heat resistance, and dimensional stability, a lower coefficient of linear thermal expansion and reduced anisotropy, and a reduced anisotropy of shrinkage during molding. [Brief explanation of the drawings]

[0015] [Figure 1A] FIG. 1 is a perspective view showing an example of glass flakes. [Figure 1B] FIG. 1B is a plan view of the glass flakes shown in FIG. 1A. [Figure 2] FIG. 1 is a cross-sectional view showing an example of a glass flake manufacturing apparatus. [Figure 3] FIG. 1 is a cross-sectional view showing an example of a chopped strand manufacturing apparatus. [Figure 4] FIG. 1 is a cross-sectional view showing an example of a chopped strand manufacturing apparatus. [Figure 5] FIG. 1 is a perspective view showing an example of a flat fiber. [Figure 6] FIG. 10 is a perspective view showing another example of a flat fiber. DETAILED DESCRIPTION OF THE INVENTION

[0016] In the following, all "%" indications of the content of each component are by weight. "Substantially free" means that the content is less than 0.1% by weight, preferably less than 0.07% by weight, and more preferably less than 0.05% by weight. In this context, "substantially" means that impurities that are inevitably mixed in from industrial raw materials are allowed, with the above-mentioned limits being met. The preferred ranges for the content, properties, and other aspects of each component can be understood by any combination of the upper and lower limits individually described below.

[0017] Even in the following cases, the characteristic temperature of the glass composition is nThe temperature at which the viscosity of the glass composition reaches 10 dPas is denoted as Tn (for example, T2.5 indicates that the viscosity of the glass composition reaches 10 2.5 (The dielectric constant refers to the temperature at which the dielectric constant becomes dPas.) Strictly speaking, the dielectric constant refers to the relative permittivity, but in this specification, it is simply referred to as the dielectric constant in accordance with conventional practice. The dielectric constant and dielectric loss tangent are values ​​at room temperature (25°C). The following explanation is not intended to limit the present invention, but is presented to show preferred embodiments thereof.

[0018] [Components of glass composition] (SiO2) SiO2 is a component that forms the network structure of glass. SiO2 has the effect of lowering the dielectric constant of the glass composition. If the SiO2 content is too low, the dielectric constant of the glass composition cannot be sufficiently reduced. If the SiO2 content is too high, the viscosity during melting becomes too high, making it difficult to obtain a homogeneous glass composition. The SiO2 content is preferably 40% or more, 45% or more, 46% or more, or even 48% or more, and particularly 49% or more. In some cases, it may be 50% or more, even 50.5% or more, 51% or more, 52% or more, or 53% or more. The SiO2 content is preferably 60% or less, less than 58%, 56% or less, or even less than 55%, particularly 54.5% or less. In some cases, it may be 54% or less, 53% or less, 52% or less, or 51% or less. An example of a preferred range of the SiO2 content is 40% or more but less than 58%, and even 40% or more but less than 55%. The SiO2 content can also be set to 40% or more and 49.95% or less.

[0019] (B2O3) B2O3 is a component that forms the network structure of glass. B2O3 reduces the dielectric constant of the glass composition, reduces the viscosity of the glass composition during melting, improves defoaming (bubble removal), and suppresses the incorporation of bubbles into the formed glass filler. However, B2O3 is easily volatilized during melting of the glass composition, and an excessive B2O3 content can make it difficult to achieve sufficient homogeneity in the glass composition or insufficiently suppress the incorporation of bubbles into the formed glass filler. The B2O3 content is preferably 25% or more, 27% or more, 29% or more, 30% or more, or even more than 30%, and in some cases may be 30.5% or more, even 31% or more, 32% or more, 33% or more, or 34% or more. The B2O3 content is preferably 45% or less, 43% or less, 41% or less, or even 39% or less, and in some cases may be 38% or less, even 36% or less, 35% or less, 34% or less, or 32% or less. An example of a preferable range for the B2O3 content is more than 30% and not more than 45%. The B2O3 content may also be 25% or more and 40% or less, 25% or more and 29.9% or less, or 31% or more and 40% or less.

[0020] (SiO2+B2O3), (SiO2+B2O3+Al2O3) To obtain a glass composition with a sufficiently low dielectric constant, the total content of SiO2 and B2O3 (SiO2 + B2O3) should be adjusted to 77% or more, 78% or more, or even 80% or more. (SiO2 + B2O3) is preferably 81% or more, 82% or more, or even 83% or more, and may be 84% or more or even 85% or more in some cases. (SiO2 + B2O3) may be 90% or less, or even 87.5% or less. This is because an excessively high (SiO2 + B2O3) value promotes the tendency of the glass composition to undergo phase separation. Furthermore, (SiO2 + B2O3) can be 70% or more. The total content of SiO2, B2O3, and Al2O3 (SiO2 + B2O3 + Al2O3) is preferably 99.9% or less to allow for other components. (SiO2 + B2O3 + Al2O3) may be 98% or less, 97% or less, less than 97%, or even 96% or less. A preferred example of a combination of (SiO2 + B2O3) and (SiO2 + B2O3 + Al2O3) is one in which (SiO2 + B2O3) is 82% or more and (SiO2 + B2O3 + Al2O3) is 98% or less. Furthermore, (SiO2 + B2O3 + Al2O3) can be 90% or more and 98% or less, or 90% or more and 97% or less.

[0021] (Preferable combination of SiO2 and B2O3) To obtain a glass composition with a lower dielectric constant and easier melting, there are preferred ranges for the SiO2 and B2O3 contents. The first combination is a combination of an SiO2 content of 48-51%, preferably 49-51%, and more preferably 50-51%, and a B2O3 content of 33-35%, preferably 34-35%. The second combination is a combination of an SiO2 content of 50-53%, preferably 51-52%, and a B2O3 content of 32-35%, preferably 32-34%. The third combination is a combination of an SiO2 content of 52-54%, preferably 52.5-54%, and a B2O3 content of 31-34%, preferably 32-34%. The fourth combination is a combination of an SiO2 content of 52-55%, preferably 53-55%, and a B2O3 content of 30-32%.

[0022] A fifth combination is a combination in which the SiO2 content is 47-52%, preferably 48-51%, more preferably 48.5-50.5%, and particularly preferably 48.95-49.95%, and the B2O3 content is 25-30%, preferably 26-29.5%, and more preferably 26-29%. In the fifth combination, the sum of the MgO content and the CaO content (MgO + CaO) is 3.5% or more, more preferably 4% or more, and suitably 8% or less. A sixth combination is a combination in which the SiO2 content is 48-53%, preferably 49-52%, more preferably 49-51.5%, and in some cases 49-51% or 48.95-49.95%, and the B2O3 content is 28-35%, preferably 30-33%, and in some cases 30.5-32.5%. In the sixth combination, (MgO+CaO) is 1% or more and less than 3.5%, preferably 1 to 3%, more preferably 1 to 2.5%, and in some cases 1.5 to 2.5%.

[0023] (Al2O3) Al2O3 is a component that forms the network structure of glass. Al2O3 has the effect of increasing the chemical durability of the glass composition. On the other hand, Al2O3 makes the glass composition more susceptible to devitrification during spinning. The Al2O3 content is preferably 5% or more, 7.5% or more, 8% or more, 9% or more, or even 10% or more, and may be 10.5% or more, 12% or more, or 13% or more in some cases. The Al2O3 content is preferably 20% or less, 18% or less, 17% or less, or even 15% or less, and may be 14% or less, or even 13% or less, or 12.5% ​​or less in some cases. An example of an Al2O3 content suitable for reliably controlling the devitrification temperature TL to a range lower than the temperature T3 is 12.3% or less. Al2O3 is generally understood to be a component that increases the viscosity of the glass composition during melting. However, in a glass composition having a high value of SiO2+B2O3, Al2O3 can specifically act to reduce the viscosity during melting.

[0024] A preferred range for the Al2O3 content is, for example, 8 to 12.5%, particularly 10 to 12.5%. When the above-mentioned first to fourth combinations of SiO2 and B2O3 contents are employed, these ranges are particularly suitable.

[0025] Another example of a preferred range for the Al2O3 content is 13 to 17%. When the fifth combination of SiO2 and B2O3 contents described above is employed, an Al2O3 content of 13 to 17% is particularly suitable. Another example of a preferred range for the Al2O3 content is 12 to 15%. When the sixth combination of SiO2 and B2O3 contents is employed, an Al2O3 content of 12 to 15% is particularly suitable.

[0026] Alkali metal oxides are well known as components that act to reduce viscosity during melting, but increasing the content of alkali metal oxides simultaneously increases the dielectric constant. In contrast, in the preferred glass composition of the present invention, Al2O3 specifically acts to reduce viscosity during melting, but only slightly increases the dielectric constant.

[0027] (MgO) MgO is an optional component that reduces the viscosity of the glass composition during melting, suppresses the incorporation of bubbles into the glass filler, and improves the homogeneity of the glass composition. The MgO content may be 0.1% or more, 0.2% or more, or even 0.5% or more, 0.6% or more, or even 0.8% or more, or even 1% or more in some cases. The MgO content is preferably less than 10%, 8% or less, 7% or less, or 5% or less in some cases, 3% or less, even 2% or less, and particularly 1.6% or less in some cases. The MgO content may be preferably 1.7% or less, 1.5% or less, even 1.2% or less, or 1% or less in some cases, in order to keep the ratio to the CaO content within an appropriate range. However, depending on the contents of other components, the optimal MgO content may be 2% or more, for example, 2 to 8%, or even 2 to 5%, or even 3 to 5%. It should be noted that MgO has a large effect of lowering the devitrification temperature, but does not increase the dielectric constant as much as the alkali metal oxide R2O. Therefore, it is preferable to add MgO preferentially to R2O, in other words, so that its content is higher than that of R2O.

[0028] An example of a preferred range for the MgO content is 0.5 to 2%. When the first to fourth combinations of the SiO2 and B2O3 content are used, the MgO content is 0.5 to 2%, and more preferably 0.5 to 1.6%. When the fifth combination of the SiO2 and B2O3 content is used, the MgO content is 0.5 to 2%, and more preferably 1 to 2%. Another example of a preferred range for the MgO content is 0.1 to 1%. When the sixth combination of the SiO2 and B2O3 content is used, the MgO content is 0.1 to 1%, and more preferably 0.1% or more and less than 1%.

[0029] (CaO) CaO is an optional component that improves the meltability of glass raw materials and reduces the viscosity of the glass composition during melting. The effect of CaO is greater than that of MgO. The CaO content may be 0.1% or more, 0.5% or more, or even 1% or more, and in some cases 1.5% or more, or even 2% or more. The CaO content is preferably less than 10%, 7% or less, or 5% or less, and in some cases 4% or less, 3.5% or less, 3% or less, or even 2.5% or less. Note that CaO has a greater effect of increasing the dielectric constant of the glass composition than MgO and ZnO. For the same reason as MgO, it is preferable to add CaO preferentially to the alkali metal oxide R2O, in other words, so that its content is higher than that of R2O.

[0030] An example of a preferred range for the CaO content is 2 to 5%, and more preferably 2 to 3.5%. When the first to fifth combinations of SiO2 and B2O3 content are used, a CaO content of 2 to 5% is particularly suitable, with 2 to 3.5% being more suitable for the first to fourth combinations and 2.5 to 5% being more suitable for the fifth combination. Another example of a preferred range for the CaO content is 0.5 to 2%. When the sixth combination of SiO2 and B2O3 content is used, a CaO content of 0.5 to 2% is particularly suitable.

[0031] A particularly preferred example of the combination of MgO and CaO contents is 1-2% MgO and 2-5% CaO, which is particularly suitable when the fifth combination of SiO2 and B2O3 contents is used.

[0032] (SrO) SrO is also an optional component that improves the meltability of glass raw materials and reduces the viscosity of the glass composition during melting. However, since SrO increases the dielectric constant of the glass composition compared with MgO and CaO, it is desirable to limit its content. The SrO content is preferably 1% or less, 0.5% or less, or even 0.1% or less. SrO may not be substantially present.

[0033] When using the first to fifth combinations of SiO2 and B2O3 contents, a SrO content of 0.1% or less is particularly suitable. In this case, SrO may be substantially absent. However, SrO may be added so that its content is 0.1 to 5%, or even 1 to 3.5%. When using the sixth combination of SiO2 and B2O3 contents, a SrO content of 0.1 to 5%, or even 1 to 3.5%, is particularly suitable. In particular, in the sixth combination, it has been discovered that SrO, contrary to the common general knowledge of those skilled in the art, can effectively reduce dielectric loss, in other words, the dielectric loss tangent. In the sixth combination, the ratio of the SrO content to the CaO content, SrO / CaO, may exceed 1. In this case, the ratio of the CaO content to the MgO content, CaO / MgO, may also exceed 1.

[0034] (RO) The RO content, i.e., the total content of MgO, CaO, and SrO, is preferably less than 15%, 12% or less, 10% or less, 9.5% or less, 8% or less, or even less than 7%, particularly preferably 6% or less, and in some cases may be 5% or less, or even 4% or less. If the RO content is too high, the dielectric constant may not be sufficiently reduced. Although each component constituting RO is individually optional, it is preferable that at least one of them is contained, i.e., the total content exceeds 0%. The RO content is preferably 1% or more, 1.5% or more, 2% or more, or even 2.5% or more, and in some cases may be 3% or more, or even 3.5% or more.

[0035] A preferred range of the RO content is, for example, 2 to 7%, particularly 2 to 4%.

[0036] (MgO / RO) The ratio of MgO / RO, i.e., the ratio of the MgO content to the RO content, is preferably less than 0.8, even less than 0.7, and may be 0.5 or less, or 0.4 or less in some cases. If the ratio of MgO / RO is large, the glass composition tends to undergo phase separation more significantly, which may impair the homogeneity of the glass composition. On the other hand, in order to suppress the dielectric constant of the glass composition, the ratio of MgO / RO is preferably 0.1 or more, even preferably 0.14 or more, and may be 0.19 or more in some cases. The ratio of MgO / RO is preferably 0.1 to 0.5.

[0037] (MgO / (MgO+CaO)) The ratio of MgO / (MgO+CaO), i.e., the ratio of the MgO content to the total content of MgO and CaO, may also be within any range combining the upper and lower limits mentioned above for MgO / RO. MgO / (MgO+CaO) is preferably 0.1 to 0.5, and particularly 0.1 to 0.4.

[0038] (LiO) Li2O is an optional component that, even in small amounts, reduces the viscosity of the glass composition during melting, suppresses the incorporation of bubbles into the glass filler, and also suppresses devitrification. Furthermore, adding an appropriate amount of Li2O significantly suppresses the tendency of the glass composition to undergo phase separation. However, although this effect is relatively weaker than that of other components such as R2O, Li2O increases the dielectric constant of the glass composition. The Li2O content is preferably 1.5% or less, 1% or less, or 0.5% or less, and may be 0.4% or less, 0.3% or less, or even 0.2% or less in some cases. The Li2O content is preferably 0.01% or more, 0.03% or more, or even 0.05% or more. The Li2O content is preferably 0.01 to 0.5%, or even 0.05 to 0.4%.

[0039] (Na2O) Na2O is also an optional component that, even in small amounts, reduces the viscosity of the glass composition during melting, inhibits the incorporation of bubbles into the glass filler, and further inhibits devitrification. From this perspective, the Na2O content may be 0.01% or more, 0.05% or more, or even 0.1% or more. However, the addition of Na2O must be limited to a limited range so as not to increase the dielectric constant of the glass composition. The Na2O content is preferably 1.5% or less, 1% or less, 0.5% or less, or even 0.4% or less, and in some cases may be 0.2% or less, further 0.15% or less, particularly 0.1% or less, 0.05% or less, or 0.01% or less. A preferred range of the Na2O content is, for example, 0.01 to 0.4%.

[0040] (K2O) K2O is also an optional component that, even in small amounts, reduces the viscosity of the glass composition during melting, inhibits the incorporation of bubbles into the glass filler, and also inhibits devitrification. However, K2O has a significant effect of increasing the dielectric constant of the glass composition. The K2O content is preferably 1% or less, 0.5% or less, or 0.2% or less, and may be 0.1% or less, 0.05% or less, or 0.01% or less in some cases. K2O need not be substantially present.

[0041] (R2O) The content of R2O and the total content of Li2O, Na2O, and K2O is preferably 5% or less, 4% or less, 3% or less, 2% or less, or even 1.5% or less, and in some cases may be 1% or less, even 0.6% or less, or 0.5% or less. Each component constituting R2O is individually optional, but it is preferable that at least one of them is contained, i.e., the total content exceeds 0%. The content of R2O is preferably 0.03% or more, 0.05% or more, or even 0.1% or more, particularly 0.15% or more, or 0.2% or more.

[0042] Furthermore, when the content of Li2O is greater than the content of Na2O, the tendency of the glass composition to undergo phase separation may be more effectively suppressed.

[0043] When the Li2O content is 0.25% or more, or even 0.3% or more, the characteristic temperature can be adjusted to a more preferable range. In particular, when the first combination of SiO2 and B2O3 contents is used, it is preferable to add Li2O so that the content is 0.25% or more, or even 0.3% or more. In this case, Na2O may be added so that the content is 0.05% or more but less than the Li2O content.

[0044] (T-Fe2O3) T-Fe2O3 is an optional component that improves the meltability of glass raw materials through its heat absorbing effect and also improves the homogeneity of the glass composition during melting. The T-Fe2O3 content is preferably 0.01% or more, 0.02% or more, 0.05% or more, or even 0.10% or more. The effect of improving meltability is significant when the T-Fe2O3 content is 0.01% or more, while the effect of improving homogeneity is particularly significant when the T-Fe2O3 content is 0.02% or more. To suppress excessive heat absorbing effect of T-Fe2O3, the T-Fe2O3 content is preferably 0.5% or less, 0.3% or less, or even 0.25% or less, and in some cases may be 0.20% or less. In accordance with conventional practice, the total iron oxide content of a glass composition is expressed herein as the value obtained by converting iron oxides other than Fe2O3, such as FeO, into Fe2O3, i.e., the T-Fe2O3 content. Therefore, at least a portion of T-Fe2O3 can be contained as Fe O. A preferred range for the content of T-Fe2O3 is, for example, 0.01 to 0.5%, and further 0.1 to 0.3%.

[0045] (ZnO) ZnO is an optional component that improves the meltability of glass raw materials and reduces the viscosity of the glass composition during melting. However, ZnO increases the dielectric constant of the glass composition. The ZnO content is preferably 3.5% or less, 2% or less, 1% or less, or even 0.5% or less. ZnO may not be substantially present.

[0046] (Other ingredients) Examples of components other than those mentioned above that may be contained in the glass composition include P2O5, BaO, PbO, TiO2, ZrO2, La2O3, Y2O3, MoO3, WO3, Nb2O5, Cr2O3, SnO2, CeO2, As2O3, Sb2O3, and SO3. Other components that may be contained in the glass composition include noble metal elements such as Pt, Rh, and Os, and halogen elements such as F and Cl. The allowable content of each of these components is preferably less than 2%, even less than 1%, and particularly less than 0.5%, and the total content is preferably less than 5%, even less than 3%, particularly less than 2%, and especially less than 1%. However, the glass composition may be substantially free of the other components mentioned above. While a trace amount of TiO2 may be added for reasons described below, it does not necessarily need to be substantially free. The same applies to ZrO2. Furthermore, it is preferable that BaO and PbO are substantially free. It is also preferable that P2O5 is substantially free. This is because BaO and PbO have a significant effect of increasing the dielectric constant of the glass composition, and P2O5 induces phase separation. Components other than the above-listed components from SiO2 to ZnO may be substantially absent. However, even in this case, the glass composition may contain components effective in promoting fining during melting, preferably SO3, F, and Cl, each in an amount of less than 2%.

[0047] It has been found that the addition of a small amount of TiO2 may decrease the dielectric constant and dielectric loss tangent of the glass composition, contrary to the common general knowledge of those skilled in the art. From this perspective, the TiO2 content may be more than 0% and not more than 1%. In particular, when the sixth combination of SiO2 and B2O3 contents is adopted, more than 0% and not more than 1% of TiO2 may be added.

[0048] (Example of a preferred composition) In one preferred embodiment, the glass composition comprises the following components: 40≦SiO2<58 25≦B2O3≦40 7.5≦Al2O3≦18 0 <R2O≦4 0≦Li2O≦1.5 0≦Na2O≦1.5 0≦K2O≦1 1≦RO<10 0≦MgO<10 0≦CaO<10 0≦SrO≦5 0≦T-Fe2O3≦0.5

[0049] In one embodiment containing the above components, 7.5≦Al2O3≦15 and 0≦SrO≦1 may be satisfied.

[0050] At the end of the above 0≦ZnO≦3.5 A glass composition containing the above is another preferred embodiment.

[0051] The glass composition of these forms preferably further satisfies 40≦SiO2<55. It may also satisfy SiO2+B2O3≧80, and preferably SiO2+B2O3+Al2O3≦99.9. MgO / RO<0.8, particularly MgO / RO<0.8 and 40≦SiO2<55, are other conditions that may be satisfied by the glass composition of the above forms.

[0052] [Characteristics of glass composition] (Dielectric constant) In a preferred embodiment, the dielectric constant of the glass composition at a measurement frequency of 1 GHz is 4.65 or less, 4.4 or less, 4.35 or less, 4.30 or less, 4.25 or less, or even 4.20 or less, and in some cases 4.18 or less. The dielectric constant at a measurement frequency of 5 GHz is 4.63 or less, 4.4 or less, 4.31 or less, 4.27 or less, 4.22 or less, or even 4.17 or less, and in some cases 4.15 or less. The dielectric constant at a measurement frequency of 10 GHz is 4.55 or less, 4.4 or less, 4.22 or less, 4.18 or less, 4.14 or less, or even 4.08 or less, and in some cases 4.06 or less.

[0053] (Dielectric tangent: tanδ) In a preferred embodiment, the dielectric loss tangent of the glass composition at a measurement frequency of 1 GHz is 0.007 or less, 0.005 or less, 0.004 or less, or even 0.003 or less, and in some cases 0.002 or less. The dielectric loss tangent at a measurement frequency of 1 GHz may be 0.001 or less, less than 0.001, 0.0009 or less, 0.0008 or less, or even 0.0007 or less. The dielectric loss tangent at a measurement frequency of 5 GHz is 0.007 or less, 0.005 or less, 0.004 or less, or even 0.003 or less, and in some cases 0.002 or less. The dielectric loss tangent at a measurement frequency of 10 GHz is 0.007 or less, 0.006 or less, 0.005 or less, 0.004 or less, or even 0.003 or less, and in some cases 0.002 or less.

[0054] (characteristic temperature) In a preferred embodiment, the T2 of the glass composition is 1700°C or less, 1650°C or less, 1640°C or less, 1620°C or less, or even 1610°C or less, and in some cases is less than 1600°C, 1550°C or less, even 1520°C or less, and particularly 1510°C or less. T2 is a temperature that serves as an indicator of the melting temperature of the glass melt. An excessively high T2 requires extremely high temperatures to melt the glass melt, resulting in high energy costs and high costs for equipment that can withstand high temperatures. At the same temperature, a glass with a lower T2 has a lower viscosity of the melt and is therefore effective in clarifying and homogenizing the glass melt. On the other hand, when melted at the same viscosity, a glass with a lower T2 can be melted at a lower temperature and is therefore suitable for mass production. T2.5 is preferably 1590°C or less, 1550°C or less, or even 1500°C or less, and in some cases 1450°C or less, even 1400°C or less. T3 is preferably 1450° C. or less, 1420° C. or less, 1400° C. or less, further 1365° C. or less, particularly 1360° C. or less, and in some cases 1330° C. or less, further 1300° C. or less. T3 is a temperature that is a guideline for molding the glass filler.

[0055] In a preferred embodiment, T3 of the glass composition is higher than the devitrification temperature TL. In a more preferred embodiment, T3 is higher than TL by 10°C or more, further 50°C or more, and in some cases 100°C or more. In a preferred embodiment, T2.5 of the glass composition is higher than the devitrification temperature TL by 50°C or more. In a more preferred embodiment, T2.5 is higher than TL by 100°C or more. T3 and T2.5 that are sufficiently higher than TL greatly contribute to stable production of glass fillers.

[0056] The fifth combination of SiO2 and B2O3 contents is particularly suitable for achieving desirable characteristic temperatures, such as T2 of 1520°C or less, particularly 1510°C or less, and T3 of 1300°C or less and higher than TL. In the first combination of SiO2 and B2O3 contents, the glass composition having a Li2O content of 0.25% or more is also suitable for achieving desirable characteristic temperatures.

[0057] [Glass filler] (Glass filler form) The form of the glass filler is not particularly limited, and may be, for example, at least one selected from glass flakes, chopped strands, milled fibers, glass powder, glass beads, flat fibers, and glass flakes. However, these forms are not strictly distinguished from one another. Two or more glass fillers having different forms may be combined and used as a filler. The form of the glass filler may be other than glass fiber. Each form will be described below.

[0058] Glass flakes, also known as flake-like glass, have a flake-like shape. The average thickness of glass flakes is, for example, 0.1 to 15 μm. As shown in FIG. 1A, the thickness of glass flakes corresponds to the distance t between the two main surfaces of glass flakes 10. FIG. 1B shows the main surface of glass flakes 10 having an area S. The average particle diameter is, for example, 0.2 to 15,000 μm. The aspect ratio of glass flakes is, for example, 2 to 1,000. The aspect ratio can be determined by dividing the average particle diameter by the average thickness. The average thickness can be determined by measuring the thickness t of 100 or more glass flakes using a scanning electron microscope (SEM) and calculating the average value. The average particle diameter of glass flakes can be determined by the particle diameter (D50) corresponding to a cumulative deposition percentage of 50% in the particle size distribution measured by laser diffraction scattering.

[0059] Glass flakes can be obtained by known methods such as the blowing method and the cup method. A manufacturing apparatus using the blowing method is shown in Figure 2. In this apparatus, a glass base 11 having a predetermined composition molten in a refractory kiln 12 is expanded into a balloon shape by gas sent into a blow nozzle 13, forming a hollow glass film 14. This hollow glass film 14 is crushed by a pair of pressure rolls 15 to obtain glass flakes 10.

[0060] Chopped strands have a shape in which glass fibers have been cut into short pieces. The fiber diameter of chopped strands is, for example, 1 to 50 μm, and the aspect ratio thereof is, for example, 2 to 1000. The aspect ratio of chopped strands can be determined by dividing the fiber length by the fiber diameter. Chopped strands can be produced, for example, using the apparatus shown in FIGS. 3 and 4.

[0061] As shown in FIG. 3 , a glass melt having a predetermined composition is melted in a refractory kiln and drawn out as numerous glass filaments 21 through a bushing 20 having numerous (e.g., 2,400) nozzles at the bottom. Cooling water is sprayed onto the glass filaments 21, and then a binder (sizing agent) 24 is applied by an application roller 23 of a binder applicator 22. The numerous glass filaments 21 coated with the binder 24 are then bundled by a reinforcing pad 25 into three strands 26, each consisting of, for example, approximately 800 glass filaments 21. Each strand 26 is traversed by a traverse finger 27 and wound onto a cylindrical tube 29 fitted to a collet 28. The cylindrical tube 29 with the wound strand 26 is removed from the collet 28, yielding a cake (strand wound body) 30.

[0062] Next, as shown in Figure 4, the cake 30 is placed in a creel 31, and the strands 26 are pulled out from the cake 30 and bundled into a strand bundle 33 by a focusing guide 32. Water or a treatment liquid is sprayed onto the strand bundle 33 by a spraying device 34. The strand bundle 33 is cut by a rotary blade 36 of a cutting device 35, and chopped strands 37 are obtained.

[0063] Milled fibers have the shape of glass fibers cut into powder. The fiber diameter of the milled fibers is, for example, 1 to 50 μm, and the aspect ratio is, for example, 2 to 500. The aspect ratio of the milled fibers can be determined by dividing the fiber length by the fiber diameter. Milled fibers can be obtained by known methods.

[0064] Glass powder is powdered glass and is produced by crushing glass. The average particle size of the glass powder is, for example, 1 to 500 μm. The particle size of the glass powder is defined as the diameter of a sphere having the same volume as a particle of the glass powder. The glass powder can be obtained by a known method.

[0065] Glass beads have a spherical or nearly spherical shape. The average particle size of glass beads is, for example, 1 to 500 μm. The particle size of glass beads is defined as the diameter of a sphere having the same volume as a glass bead particle. Glass beads can be obtained by known methods.

[0066] A flat fiber has a shape obtained by cutting a glass fiber having a flat cross section such as an oval. As shown in FIG. 5, the major diameter D2 of the cross section of the flat fiber is larger than the minor diameter D1, with D2 / D1 being, for example, 1.2 or more. The minor diameter D1 is, for example, 0.5 to 25 μm. The major diameter D2 is, for example, 0.6 to 300 μm. The length L of the flat fiber is, for example, 10 to 1000 μm. The flat fiber can be obtained by a known method. As shown in FIG. 6, the cross section of the flat fiber may have a concave shape in which the surface extending along the major diameter D2 is recessed more at the center than at the ends.

[0067] The glass flakes are thin glass flakes. The glass flakes may be composed of glass flakes having an average thickness of 0.1 to 2.0 μm, for example, or may contain glass flakes having a thickness in the range of 0.01 to 2.0 μm at a ratio of 90 mass % or more. Glass flakes having such a small average thickness and small thickness variation are highly effective in reinforcing resins and are also excellent in reducing the molding shrinkage rate of resins.

[0068] The glass flakes are also suitable for alleviating restrictions on the thickness of resin molded articles compared to conventional methods. The glass flakes are preferably composed of glass flakes having an average thickness of 0.1 to 1.0 μm. The glass flakes preferably contain glass flakes having a thickness in the range of 0.05 to 1.0 μm in a proportion of 90 mass % or more. The glass flakes can be obtained by the above-mentioned method.

[0069] (Granulation of glass filler) At least a portion of the glass filler may be granulated. Granulation is a process in which the glass filler is subjected to a binder treatment, and the individual glass fillers are bound together by the binder to form granules. Granular flake glass has low shattering properties and is therefore easy to work with, and also has excellent dispersibility in resin. The use of granular flake glass improves feeding properties, enabling more reliable quantitative feeding. The binder used for granulation will be described below.

[0070] The binder preferably contains a surfactant and a binding component. The surfactant may be anionic, cationic, amphoteric, or nonionic. However, when the binding component contains an epoxy resin or urethane resin, a nonionic surfactant is preferred. This is because it can suppress binder aggregation and stabilize the binder. Examples of anionic surfactants include sodium dioctyl sulfosuccinate, fatty acid salts, alkyl sulfate ester salts, alkyl sulfonates, alkylaryl sulfonates, alkylnaphthalene sulfonates, alkyl sulfosuccinate salts, alkyl diphenyl ether disulfonates, alkyl phosphates, polyoxyethylene alkyl sulfate ester salts, polyoxyethylene alkylaryl sulfate ester salts, and sulfosuccinate ester salts. Examples of cationic surfactants include higher amine halogen salts, alkyl pyridinium halides, and quaternary ammonium salts. Examples of amphoteric surfactants include lauryl aminopropionate and lauryl dimethyl betaine. Examples of nonionic surfactants include polyoxyethylene lauryl ether, polyoxyethylene higher alcohol ether, polyoxyethylene octylphenyl ether and other polyoxyethylene glycol alkyl ethers, polyethylene glycol fatty acid esters such as polyethylene glycol monostearate, sorbitan monolaurate, polyoxyethylene sorbitan monolaurate and other sorbitan fatty acid esters, glycol monostearate and other glycol fatty acid esters, fatty acid monoglycerides, etc. Two or more of these may be used in combination.

[0071] The binder's binding component is not particularly limited, and organic or inorganic components can be used. Examples of organic binding components include methyl cellulose, carboxymethyl cellulose, starch, carboxymethyl starch, hydroxyethyl cellulose, hydroxypropyl cellulose, polyvinyl alcohol, silane coupling agents, acrylic resins, epoxy resins, phenolic resins, vinyl acetate, and urethane resins. Examples of inorganic binding components include water glass, colloidal silica, colloidal alumina, and aminosilanes. The binding component preferably contains at least one selected from silane coupling agents, epoxy resins, and urethane resins. Silane coupling agents have two or more reactive groups in their molecules, one of which reacts with the surface of the glass flakes and the other with the organic binding component and the thermoplastic resin, improving the compatibility between the glass flakes and the thermoplastic resin. Epoxy resins and urethane resins have good compatibility with silane coupling agents and thermoplastic resins.

[0072] The binder is preferably prepared using water or alcohol as a solvent, and its concentration is adjusted so that each component is uniformly distributed on the surface of the glass filler. The binder concentration is preferably 1 to 10 mass % in terms of total solids concentration. The binder can be prepared, for example, by adding a binding component, a surfactant, etc. to a solvent at room temperature and atmospheric pressure, and stirring until the mixture is uniform.

[0073] The ratio of the binder in the granulated glass filler, in other words, the binder adhesion rate, is, for example, 0.1 to 2 mass% in terms of solid mass ratio. An adhesion rate of 0.1 mass% or more is suitable for sufficiently suppressing the scattering of the glass filler. An adhesion rate of 2 mass% or less is suitable for suppressing gas generation and discoloration of the resin composition during extrusion molding of the resin composition.

[0074] The method for granulating the glass filler is not particularly limited, and examples thereof include agitation granulation, fluidized bed granulation, spray granulation, and rotary granulation. Specifically, a method can be applied in which a glass filler to which an appropriate amount of binder has been attached by spraying or the like is spread in a rotating drum or on a vibrating tray, and granulated while being heated to evaporate the solvent. Granular glass filler of a desired size can be produced by appropriately adjusting the rotation speed of the rotating drum or the vibration frequency of the vibrating tray, as well as the evaporation rate of the solvent.

[0075] The surface of the glass filler may be treated with a surface treatment agent. This treatment may improve the reinforcing effect of the glass filler. Examples of the surface treatment agent include silicon-based coupling agents such as γ-aminopropyltriethoxysilane, vinyltriethoxysilane, and γ-methacryloxypropyltrimethoxysilane, and titanium-based coupling agents. The amount of the surface treatment agent used is, for example, 0.05 to 0.20 mass % of the glass filler.

[0076] (Method for manufacturing glass filler) The glass filler is produced by a method including the steps of melting the glass composition described above and forming the molten glass composition into a desired glass filler. The temperature at which the glass composition is melted is, for example, 1400°C or higher.

[0077] The glass filler can also be produced by a method including the steps of melting glass raw materials prepared to obtain a glass composition constituting the glass filler, and forming the molten glass raw materials into the glass filler. The temperature for melting the glass raw materials is, for example, 1400°C or higher.

[0078] [Resin composition] The resin composition according to the present invention contains a thermoplastic resin together with the glass filler according to the present invention. The thermoplastic resin is not particularly limited, but examples thereof include polyvinyl chloride, polypropylene, polyethylene, polystyrene, polyester, polyamide, polycarbonate, polybutylene, polybutylene terephthalate, and copolymers thereof. The use of polybutylene terephthalate enhances the effects of suppressing warpage and improving dimensional stability of molded articles when mixed with the glass filler.

[0079] The content of glass filler such as glass flakes in the resin composition is preferably 5 to 70% by mass. By setting the content to 5% by mass or more, the glass filler is more likely to fully exhibit its function as a reinforcing material. By setting the content to 70% by mass or less, it becomes easier to uniformly disperse the glass filler in the resin composition. In order to sufficiently suppress molding shrinkage, the content of glass filler is more preferably 30% by mass or more.

[0080] The resin composition may contain a reinforcing material other than the glass filler as appropriate. For example, in applications requiring high strength, glass fibers may be contained. In this case, the glass fibers may be added at a content similar to that of the glass filler.

[0081] Glass flakes, flat fibers, and thin glass flakes have a relatively large specific surface area and are suitable for ensuring bonding strength with thermoplastic resins. From this perspective, the flat fiber shown in Figure 6 is preferable because its concave surface shape contributes to increasing the specific surface area.

[0082] The resin composition according to the present invention has a low dielectric constant and is suitable for improving various properties such as improved strength, heat resistance, and dimensional stability, a lower coefficient of linear thermal expansion and reduced anisotropy, and a reduced anisotropy of shrinkage during molding. [Example]

[0083] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0084] Glass raw materials were weighed to obtain the compositions shown in Tables 1 to 6 (component contents are expressed in weight %) and mixed to a homogeneous state to prepare glass raw material mixed batches. The prepared mixed batches were then placed in a platinum-rhodium crucible and heated in an indirect heating electric furnace set at 1600°C in an air atmosphere for 3 hours or more to obtain molten glass. The obtained molten glass was then poured into a refractory mold for casting, and the obtained molded body was then slowly cooled to room temperature in an annealing furnace to prepare glass composition samples to be used for evaluation.

[0085] The glass samples thus prepared were evaluated for characteristic temperatures T2, T2.5, and T3, devitrification temperature TL, and dielectric constant and dielectric loss tangent at frequencies of 1 GHz, 5 GHz, and 10 GHz. The evaluation methods are as follows.

[0086] (characteristic temperature) The viscosity was measured using the platinum ball pull-up method, and the viscosity was 10 2 dPa·s, 10 2.5 dPa·s, 10 3 The temperatures at which the viscosity becomes dPa·s are designated as T2, T2.5, and T3, respectively.

[0087] (devitrification temperature) The sample glass was crushed and passed through a sieve with 2.83 mm openings, and the particles remaining on a sieve with 1.00 mm openings were sieved. The particles were washed to remove any fine powder adhering to the particles, and then dried to prepare a sample for measuring the devitrification temperature. 25 g of the sample for measuring the devitrification temperature was placed in a platinum boat (a rectangular platinum vessel without a lid) so that the thickness was approximately uniform, and the boat was left in a temperature gradient furnace for 2 hours, after which it was removed from the furnace. The maximum temperature at which devitrification was observed inside the glass was recorded as the devitrification temperature.

[0088] (Water resistance test) The water resistance test was conducted based on a dissolution test in accordance with the Japan Optical Glass Industry Association standard JOGIS 06:1999, "Method for measuring the chemical durability of optical glass (powder method)." Specifically, the test was carried out as follows: The sample glass was crushed, passed through a 600 μm sieve, and the particles remaining on a 425 μm sieve were sieved. The particles were washed with methanol to remove any fine particles adhering to the particles, and then dried to prepare a sample for the water resistance test. A weight (g) equal to the specific gravity of the water resistance test sample was weighed into a round-bottom flask, 80 mL of pure water was added, the flask was stoppered, and the flask was kept at a temperature of 99°C or higher for 1 hour for dissolution treatment. The sample after dissolution treatment was washed with methanol, and the remaining sample after drying was weighed, and the weight loss was calculated as a percentage.

[0089] (Dielectric constant and dielectric loss tangent) The dielectric constant and dielectric loss tangent at each frequency were measured using a dielectric constant measurement device using a cavity resonator perturbation method. The measurement temperature was 25°C, and the dimensions of the measurement sample were a rectangular parallelepiped with a base of 1.5 cm on each side and a length of 10 cm.

[0090] The glass compositions of Examples 1 to 44 and 48 to 96 had a dielectric constant of 4.65 or less at a measurement frequency of 1 GHz, a T2 of 1700°C or less, and a T3 of 1450°C or less. Some of these glass compositions had a dielectric constant of 4.4 or less at a measurement frequency of 1 GHz, and the glass compositions of Examples 1 to 43, 48 to 81, 83 to 84, and 93 to 96 had a dielectric constant of 4.36 or less at a measurement frequency of 1 GHz. The glass compositions of Examples 1 to 41, 48 to 81, 83 to 84, and 93 to 96 had a dielectric constant of 4.35 or less at a measurement frequency of 1 GHz. Furthermore, the glass compositions of Examples 5 to 6, 66 to 67, and 83 to 92 had a T2 of 1520°C or less and a T3 of 1300°C or less, which were higher than the TL. The glass compositions of Examples 66-67 and 83-92 had a B2O3 content of 35% or less, and in some cases 30% or less, and had a T2 of 1520°C or less and a T3 of 1300°C or less, which was higher than TL. The glass compositions of Examples 2 and 93-96 had a dielectric loss tangent of less than 0.001 at a frequency of 1 GHz. The glass compositions of Examples 93-96 had a dielectric loss tangent of less than 0.001 at a frequency of 1 GHz and a T2 of less than 1600°C. The glass compositions of Examples 45-47 are comparative examples, and Example 45 had a T2 of more than 1700°C, and Examples 46-47 had a dielectric constant of more than 4.7 at a measurement frequency of 1 GHz.

[0091] [Table 1]

[0092] [Table 2]

[0093] [Table 3]

[0094] [Table 4]

[0095] [Table 5]

[0096]

Table 6

Claims

1. Expressed in weight percent, 40≦SiO 2 ≦60 25≦B 2 O 3 ≦45 10.5≦Al 2 O 3 ≦18 0<R 2 O≦5 0≦RO≦12 0.01≦T-Fe 2 O 3 ≦0.5 Including, SiO 2 + B 2 O 3 ≥ 82, SiO 2 + B 2 O 3 + Al 2 O 3 ≤ 98, and Li 2 O > Na 2 O holds true. A glass filler comprising a glass composition. However, R 2 O is Li 2 O, Na 2 O and K 2 RO is at least one oxide selected from MgO, CaO and SrO.

2. Expressed in weight percent, 40≦SiO 2 ≦60 25≦B 2 O 3 ≦45 10.5≦Al 2 O 3 ≦15 0<R 2 O≦5 3≦RO≦12 Including, SiO 2 + B 2 O 3 ≥ 82, SiO 2 + B 2 O 3 + Al 2 O 3 ≤ 98, 1 ≤ MgO ≤ 2, and 2 ≤ CaO ≤ 5 holds true. A glass filler comprising a glass composition. However, R 2 O is Li 2 O, Na 2 O and K 2 RO is at least one oxide selected from MgO, CaO and SrO.

3. Expressed in weight percent, 40≦SiO 2 ≦60 25≦B 2 O 3 ≦45 <h2 style=";text-align:left;direction:ltr">0<Al<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> ≦18 0<R 2 O≦5 2.16≦RO≦12 Including, i) SiO 2 +B 2 O 3 ≧80, and SiO 2 +B 2 O 3 +Al 2 O 3 ≦99.9, and ii) SiO 2 + B 2 O 3 ≥ 78, SiO 2 + B 2 O 3 + Al 2 O 3 ≤ 99.9, and 0 < RO < 10 At least one of 2.16≦SrO≦5 holds true. A glass filler comprising a glass composition. However, R 2 O is Li 2 O, Na 2 O and K 2 RO is at least one oxide selected from MgO, CaO and SrO.

4. The glass composition comprises, expressed in weight percent: 30<B 2 O 3 ≦45 The glass filler according to claim 3, comprising:

5. The glass composition comprises, expressed in weight percent: 40≦SiO 2 <58 The glass filler according to any one of claims 1 to 4, comprising:

6. The glass composition comprises, expressed in weight percent: 40≦SiO 2 <55 The glass filler according to claim 5 , comprising:

7. The glass composition comprises, expressed in weight percent: SiO 2 +B 2 O 3 ≧82 Yes 2 +B 2 O 3 +Al 2 O 3 ≦98 The glass filler according to claim 3 , wherein the following formula is satisfied:

8. Expressed in weight percent, 40≦SiO 2 <58 25≦B 2 O 3 ≦40 10.5≦Al 2 O 3 ≦15 0<R 2 O≦4 0.01≦Li 2 O≦1.5 0≦Na 2 O≦1.5 0≦K 2 O≦1 3≦RO<10 1≦MgO≦2 2≦CaO≦5 0≦SrO≦5 0.01≦T-Fe 2 O 3 ≦0.5 Including Li 2 O>Na 2 The glass filler according to claim 1 or 2, wherein O holds true.

9. Expressed in weight percent, 40≦SiO 2 <58 25≦B 2 O 3 ≦40 7.5≦Al 2 O 3 ≦18 0<R 2 O≦4 0≦Li 2 O≦1.5 0≦Na 2 O≦1.5 0≦K 2 O≦1 2.16≦RO<10 0≦MgO<10 0≦CaO<10 2.16≦SrO≦5 0≦T-Fe 2 O 3 ≦0.5 The glass filler according to claim 3, comprising:

10. The glass composition comprises, expressed in weight percent: 48≦SiO 2 ≦51 33≦B 2 O 3 ≦35 The glass filler according to any one of claims 1 to 9, comprising:

11. The glass composition comprises, expressed in weight percent: 50≦SiO 2 ≦53 32≦B 2 O 3 ≦35 The glass filler according to any one of claims 1 to 9, comprising:

12. The glass composition comprises, expressed in weight percent: 52≦SiO 2 ≦54 31≦B 2 O 3 ≦34 The glass filler according to any one of claims 1 to 9, comprising:

13. The glass composition comprises, expressed in weight percent: 52≦SiO 2 ≦55 30≦B 2 O 3 ≦32 The glass filler according to any one of claims 1 to 9, comprising:

14. The glass composition comprises, expressed in weight percent: 47≦SiO 2 ≦52 25≦B 2 O 3 ≦30 The glass filler according to any one of claims 1 to 4, comprising:

15. The glass composition comprises, expressed in weight percent: 48≦SiO 2 ≦53 28≦B 2 O 3 ≦35 1≦MgO+CaO<3.5 The glass filler according to claim 3 or 9, comprising:

16. The glass composition comprises, expressed in weight percent: 8≦Al 2 O 3 ≦12.5 The glass filler according to claim 9, comprising:

17. The glass composition comprises, expressed in weight percent: 10≦Al 2 O 3 ≦12.5 The glass filler according to claim 16, comprising:

18. The glass composition comprises, expressed in weight percent: 13≦Al 2 O 3 ≦17 The glass filler according to claim 1 or 3, comprising:

19. The glass composition comprises, expressed in weight percent: 12≦Al 2 O 3 ≦15 The glass filler according to any one of claims 1 to 15, comprising:

20. The glass composition comprises, expressed in weight percent: 0.01≦Li 2 O 3 ≦0.5 The glass filler according to any one of claims 1 to 19, comprising:

21. The glass composition comprises, expressed in weight percent: 0.05≦Li 2 O≦0.4 The glass filler according to claim 20, comprising:

22. The glass composition comprises, expressed in weight percent: 0.01≦Na 2 O≦0.4 The glass filler according to any one of claims 1 to 21, comprising:

23. The glass composition comprises, expressed in weight percent: Li 2 O>Na 2 O The glass filler according to claim 2 or 3, wherein the following formula is satisfied:

24. The glass composition comprises, expressed in weight percent: 0.5≦MgO≦1.6 The glass filler according to claim 1 or 3, comprising:

25. The glass composition comprises, expressed in weight percent: 2≦CaO≦3.5 The glass filler according to any one of claims 1 to 24, comprising:

26. The glass composition comprises, expressed in weight percent: 0.1≦SrO≦5 The glass filler according to claim 1 or 2, comprising:

27. The glass composition comprises, expressed in weight percent: 0.1≦MgO≦1 The glass filler according to claim 1 or 3, comprising:

28. The glass composition comprises, expressed in weight percent: 0.5≦CaO≦2 28. The glass filler according to claim 27, comprising:

29. The glass composition comprises, expressed in weight percent: 2≦MgO+CaO+SrO≦7 29. The glass filler according to claim 27 or 28, comprising:

30. The glass composition comprises, expressed in weight percent: 2≦MgO+CaO+SrO≦4 The glass filler according to claim 1 or 3, comprising:

31. The glass composition comprises, expressed in weight percent: 1≦MgO≦2 2≦CaO≦5 The glass filler according to claim 1 or 3, comprising:

32. The glass composition comprises, expressed in weight percent: 0.01≦T-Fe 2 O 3 ≦0.5 The glass filler according to claim 2 or 3, comprising:

33. The glass composition comprises, expressed in weight percent: 0.1≦T-Fe 2 O 3 ≦0.3 The glass filler according to any one of claims 1 to 32, comprising:

34. In the glass composition, expressed in weight percent, MgO / RO<0.8 The glass filler according to any one of claims 1 to 33, wherein the following formula is satisfied:

35. In the glass composition, expressed in weight percent, 0.1≦MgO / RO≦0.5 The glass filler according to claim 34, wherein the following formula is satisfied:

36. In the glass composition, expressed in weight percent, 0.1≦MgO / (MgO+CaO)≦0.5 The glass filler according to any one of claims 1 to 35, wherein the following formula is satisfied:

37. In the glass composition, expressed in weight percent, The glass filler according to any one of claims 1 to 36, which is substantially free of BaO and PbO.

38. In the glass composition, expressed in weight percent, TiO 2 The glass filler according to any one of claims 1 to 37, which is substantially free of:

39. In the glass composition, expressed in weight percent, 0<T+O 2 ≦1 The glass filler according to any one of claims 1 to 37, comprising:

40. The glass composition has a dielectric constant of 4.35 or less at a frequency of 1 GHz; The glass filler according to any one of claims 1 to 39,

41. The glass composition has a dielectric loss tangent of 0.007 or less at a frequency of 1 GHz; The glass filler according to any one of claims 1 to 40,

42. The glass composition has a viscosity of 10 2 The temperature T2 at which the hardness becomes dPas is 1650° C. or less, The glass filler according to any one of claims 1 to 41,

43. The glass composition has a viscosity of 10 2 The temperature T2 at which the hardness becomes dPas is 1610° C. or lower, 43. The glass filler according to claim 42,

44. The glass composition has a viscosity of 10 3 The glass filler according to any one of claims 1 to 43, wherein a temperature T3 at which the glass composition has a viscosity of 100 dPas is higher than a devitrification temperature TL of the glass composition.

45. The glass filler according to any one of claims 1 to 44, which corresponds to at least one selected from flake glass, chopped strands, milled fibers, glass powder, glass beads, flat fibers, and thin glass flakes.

46. 46. ​​The glass filler according to claim 45, which is glass flake.

47. 46. ​​The glass filler according to claim 45, which is a chopped strand.

48. 46. ​​The glass filler according to claim 45, which is a milled fiber.

49. 46. ​​The glass filler according to claim 45, which is a glass powder.

50. 46. ​​The glass filler according to claim 45, which is a glass bead.

51. 46. ​​The glass filler according to claim 45, which is a flat fiber.

52. 46. ​​The glass filler according to claim 45, which is glass flake.

53. A resin composition comprising the glass filler according to any one of claims 1 to 52 and a thermoplastic resin.

54. A method for producing a glass filler, comprising the steps of melting the glass composition according to any one of claims 1 to 3, and forming the molten glass composition into a glass filler.

55. A method for producing a glass filler according to any one of claims 1 to 52, comprising the steps of: A method for producing a glass filler, comprising: a step of melting glass raw materials prepared so as to obtain a glass composition constituting the glass filler; and a step of forming the molten glass raw materials into the glass filler.

Citation Information

Patent Citations

  • Glass fiber with low permittivity

    CN101012105A

  • Glass fiber having low dielectric constant

    JP1987226839A

  • Glass fiber composition having low dielectric constant

    JP1989051345A

  • Glass composition for glass fiber, glass fiber and glass fiber sheet-like material

    JP2009286686A

  • Low dielectric fiberglass

    JP2010508226A